2012
DOI: 10.21059/buletinpeternak.v36i1.1276
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS PENDAPATAN USAHA PETERNAKAN AYAM BURAS (Studi Kasus di Kecamatan Tegalombo, Kabupaten Pacitan)

Abstract: INTISARIPenelitian bertujuan untuk mengetahui besarnya pendapatan yang diperoleh peternak ayam buras dan pengaruh faktor-faktor produksi terhadap pendapatan usaha peternakan ayam buras di Kecamatan Tegalombo Kabupaten Pacitan. Penelitian dilaksanakan di Desa Kemuning, Desa Tegalombo dan Desa Tahunan mulai tanggal 3 Januari sampai 4 Februari 2011. Metode yang digunakan dalam penelitian adalah metode survei dengan wawancara langsung kepada 30 peternak dan pengambilan lokasi dilakukan secara sengaja (purposive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
3
0
8
Order By: Relevance
“…The only variable that significantly decrease income was mortality (-0.106) with P<0.10, while body weight of chicken sold, 75 days was completely not significant. The result was in line with previous study reported by Dewanti and Sihombing ( 2012) that hatching rate and cost of production had a significant influence to the income of semi intensive and intensive native chicken farmer therefore semi intensive native chicken rearing could be more economical for the small holder poultry keepers (Sanka and Mbaga, 2014). Hatching rate determined the farmer's income because the higher of hatching rate, farmer can sold the more eggs and obtain more income.…”
Section: Factors Influencing the Incomesupporting
confidence: 92%
“…The only variable that significantly decrease income was mortality (-0.106) with P<0.10, while body weight of chicken sold, 75 days was completely not significant. The result was in line with previous study reported by Dewanti and Sihombing ( 2012) that hatching rate and cost of production had a significant influence to the income of semi intensive and intensive native chicken farmer therefore semi intensive native chicken rearing could be more economical for the small holder poultry keepers (Sanka and Mbaga, 2014). Hatching rate determined the farmer's income because the higher of hatching rate, farmer can sold the more eggs and obtain more income.…”
Section: Factors Influencing the Incomesupporting
confidence: 92%
“…Penerimaan diperhitungkan dalam bentuk tunai yang diterima oleh peternak dari hasil penjualan (Dewanti & Sihombing, 2012 Nilai biaya produksi yang relatif besar dan cenderung seimbang dengan skala usaha dapat meningkatkan penerimaan peternak sehingga semakin besar pula resiko yang dihadapi sehingga perlu meningkatkan sistem pengelolaan secara optimal (Azizah dkk., 2013). S a t u kali siklus produksi jumlah ternak yang dipanen mencapai 94 persen dengan angka mortalitas sebanyak 6 persen, lebih tinggi daripada mortalitas standar yaitu 4,5 persen.…”
Section: Penerimaanunclassified
“…Besaran biaya tenaga kerja peternak, berdasarkan jumlah dan waktu kerja yang digunaan untuk mengurus ayam kampung milik sendiri biasanya tdak dihitung (Dewanti dan Sihombing 2012). Data empiris adalah data yang diperoleh kemudian diuji terlebih dahulu, sehingga dapat diketahui nilai ekoomi pada beberapa model usaha baik industri maupun usaha peterak (Istikomah et al, 2016).…”
Section: Analisis Dataunclassified